THE EFFECT OF OIL CONTENT ON SONIC WAVE PROPAGATION (Analyses from Well Log Data) - Suprajitno Munadi (Testing Center for Oil and Gas LEMIGAS, 2007)
The effect of fluid content to the sonic wave propagation in the reservoir rock hasbeen studied experimentally using the well log data. Evidence shows that the water contentaffects the sonic wave propagation only in a specific interval, while oil content also affectsthe sonic wave propagation but at a specific low interval. There is a discontinuity wherethe effect of oil content changes suddenly with an increasing oil content. Higher than thisvalue it seems that there is no effect of oil content on sonic wave transit time.